Effects of vascular risk factors, statins, and antihypertensive drugs on PiB deposition in cognitively normal subjects. Issue 1 (19th April 2016) - Glodzik, Lidia; Rusinek, Henry; Kamer, Angela; Pirraglia, Elizabeth; Tsui, Wai; Mosconi, Lisa; Li, Yi; McHugh, Pauline; Murray, John; Williams, Schantel; Osorio, Ricardo S.; Randall, Catherine; et al.
Abstract: Introduction: Hypertension, hypercholesterolemia, and obesity increase the risk of dementia. Although their detection is commonly followed by an introduction of treatment, little is known about how medications frequently used to treat vascular risk affect amyloid deposition. Methods: A cross‐sectional study of 156 subjects who underwent positron emission tomography with PiB. Using linear regression, we tested whether blood pressure, cholesterol, overweight/obese status, angiotensin receptor blockers (ARBs), beta‐blockers, diuretics, angiotensin converting enzyme inhibitors, and statins predicted amyloid deposition. Results: The use of ARBs (β = −.15, P  = .044) and diuretics (β = −.20, P  = .006) predicted less amyloid accumulation; older age (β = .29, P  < .001) and statins (β = .23, P  = .004) were related to greater amyloid deposition. Overweight and/or obese women had more cortical amyloid than their peers. Discussion: Prospective studies should confirm effects of drugs and increased body weight on amyloid accumulation and establish whether they translate into measurable clinical outcomes. Women may be more susceptible to harmful effects of obesity.